2017
DOI: 10.1002/14651858.cd012597
|View full text |Cite
|
Sign up to set email alerts
|

Saline irrigation for allergic rhinitis

Abstract: Background Allergic rhinitis is a common condition affecting both adults and children. Patients experience symptoms of nasal obstruction, rhinorrhoea, sneezing and nasal itching, which may affect their quality of life. Nasal irrigation with saline (salty water), also known as nasal douching, washing or lavage, is a procedure that rinses the nasal cavity with isotonic or hypertonic saline solutions. It can be performed with low positive pressure from a spray, pump or squirt bottle, with a nebuliser or with grav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 18 publications
1
44
0
Order By: Relevance
“…The patient questionnaire was developed based on the available literature 13‐17 and expert opinion and consisted of questions regarding general personal information, devices used, saline solution concentration, and effectiveness scores ranging from 0 to 10 (0 = strongly disagree, 10 = strongly agree) that covered disease severity, convenience of use, learning curve, and device satisfaction. For patients who had used more than one device, their opinions regarding the device they most recently used were collected.…”
Section: Methodsmentioning
confidence: 99%
“…The patient questionnaire was developed based on the available literature 13‐17 and expert opinion and consisted of questions regarding general personal information, devices used, saline solution concentration, and effectiveness scores ranging from 0 to 10 (0 = strongly disagree, 10 = strongly agree) that covered disease severity, convenience of use, learning curve, and device satisfaction. For patients who had used more than one device, their opinions regarding the device they most recently used were collected.…”
Section: Methodsmentioning
confidence: 99%
“…Many over-the-counter treatments claim to alleviate nasal symptoms, but their efficacy remains largely unproven [4]. In nasal saline irrigation (NSI) the patient rinses nasal cavities by instilling either isotonic or hypertonic saline solution into one nostril and allows it to drain out from the other nostril [5][6][7][8]. Some believe it is an efficient, cheap and safe alternative treatment [9].…”
Section: Introductionmentioning
confidence: 99%
“…2 CliniCal boTTom line: This Cochrane review showed that people who suffer from allergic rhinitis benefitted from using saline irrigation both in the short and long-term. 3 No adverse effects were reportedly associated with the use of saline irrigation but it is unclear how competently the studies carried out this assessment. 3 There was no evidence to suggest that saline irrigation was less effective than nasal corticosteroids or antihistamines but this may have been due to a lack of available evidence.…”
mentioning
confidence: 99%
“…3 No adverse effects were reportedly associated with the use of saline irrigation but it is unclear how competently the studies carried out this assessment. 3 There was no evidence to suggest that saline irrigation was less effective than nasal corticosteroids or antihistamines but this may have been due to a lack of available evidence. 3 No harms with respect to saline irrigation were identified.…”
mentioning
confidence: 99%
See 1 more Smart Citation